Thực trạng giáo dục giới tính cho học sinh ở một số trường trung học cơ sở khu vực phía Nam - Nguyễn, Minh Trí (Tạp chí Giáo dục, 2024)
Sex education is one of the critical action programs to promote gender equality and achieve the goal of sustainable development by 2030. However, in general, even parents are not fully aware of the importance of sex education for their children. In addition, communication between teachers and students about gender knowledge is still limited. Accordingly, sex education for students is an urgent task in the current context, especially for secondary school students who are entering puberty, a physiological and psychological period with many changes significant change. The article presents the current status of sex education for students at some secondary schools in the Southern region and at home and surveys students' level of awareness on this issue. The research results will be the basis for providing solutions for promoting sex education for students in general and secondary school students in particular.